Human Dignity Concepts in Judicial Reasoning. Study of National and International Law - Doroszewska, Katarzyna (Review of European and Comparative Law, 2020)
Many modern legal systems declare, that protection of human dignity plays an important role in its construction. Therefore, a question may be asked if the concept of dignity is similar in different legal systems. The following paper presents the results of the research on human dignity concepts in reasoning of national (Polish and German Supreme Courts) and international courts (ICC, ECHR). Both national systems provide a constitutional protection of human dignity, Rome Statute, which constitutes the ICC, prohibits behaviours infringing dignity (model of Geneva Conventions), whereas the European Convention of Human Rights does not include the term “human dignity”, only prohibition of torture or “inhuman or degrading treatment”, what is understood as protection of dignity. On the basis of the research there could be stated, that each legal system has developed its own concept of human dignity, although all concepts have a similar core, as nearly all ways of understanding “protection of human dignity” are combined with a commitment to respect each person. This kind of respect could be assumed as a basis of human dignity protection.